The Catalytic Asymmetric Construction of Trifluoromethylated Quaternary Carbon-Containing Thiochromans - Chen, Hui; Wang, Cui; Wen, Dongwa; Deng, Yabo; Liu, Xin; Liu, Xueting; Zhang, Jiang; Yan, Wenjin (Synthesis, 2019)
Trifluoromethylated chiral quaternary stereogenic carbon center at 2-position of thiochromans has been constructed through organocatalyzed Michael-aldol reaction. With quinine squaramide as catalyst, the reaction of 2-mercaptobenzaldehyde with β-aryl-β-CF3 enones or β-alkyl-β-CF3 enones gave 2-CF3-thiochromans bearing three contiguous stereogenic centers in good to excellent diastereoselectivities, enantioselectivities, and yields.
Keywords: cascade reaction; asymmetric catalysis; orgnocatalytic; CF3-containing; sulfur-containing heterocycle